Neonatal and child mortality data in retrospective population-based surveys compared with prospective demographic surveillance: EN-INDEPTH study - Tryphena Nareeba; Francis Dzabeng; Nurul Alam; Gashaw A. Biks; Sanne M. Thysen; Joseph Akuze; Hannah Blencowe; Stephane Helleringer; Joy E. Lawn; Kaiser Mahmud; Temesgen Azemeraw Yitayew; Ane B. Fisker; et al. (BMC, 2021)
Abstract Background Global mortality estimates remain heavily dependent on household surveys in low- and middle-income countries, where most under-five deaths occur. Few studies have assessed the accuracy of mortality data or determinants of capturing births in surveys. Methods The Every Newborn-INDEPTH study (EN-INDEPTH) included a large, multi-country survey of women aged 15-49 interviewed about livebirths and their survival status in five Health and Demographic Surveillance Systems (HDSSs). The HDSSs undertake regular household visits to register births and deaths for a given population. We analysed EN-INDEPTH survey data to assess background factors associated with not recalling a complete date-of-birth. We calculated Kaplan-Meier survival estimates for both survey and HDSS data and describe age-at-death distributions during the past 5 years for children born to the same women. We assessed the proportion of HDSS-births that could be matched on month-of-birth to survey-births and used regression models to identify factors associated with matching. Results 69,176 women interviewed in the survey reported 109,817 births and 3064 deaths in children under 5 years in the 5 years prior to the survey. In the HDSS data, the same women had 83,768 registered births and 2335 under-five deaths in the same period. A complete date-of-birth was not reported for 1-7% of survey-births. Birthdates were less likely to be complete for dead children and children born to women of higher parity or with little/no education. Distributions of reported age-at-death indicated heaping at full weeks (neonatal period) and at 12 months. Heaping was more pronounced in the survey data. Survey estimates of under-five mortality rates were similar to HDSS estimates of under-five mortality in two of five sites, higher in the survey in two sites (15%, 41%) and lower (24%) in one site. The proportion of HDSS-births matched to survey-births ranged from 51 to 89% across HDSSs and births of children who had died were less likely to be matched. Conclusions Mortality estimates in the survey and HDSS were not markedly different for most sites. However, neither source is a "gold standard" and both sources miss some events. Research is required to improve capture and accuracy to better track newborn and child survival targets.